1992
DOI: 10.1007/bf00400853
|View full text |Cite
|
Sign up to set email alerts
|

Mumps virus infects Beta cells in human fetal islet cell cultures upregulating the expression of HLA class I molecules

Abstract: The ability of mumps virus to infect pancreatic Beta cells and cause alterations in their HLA expression was evaluated in cultured human fetal islet cell clusters. Mumps virus could be isolated during the whole culture period (6-8 days) and 60% of cells, including Beta cells, contained viral nucleocapsid protein at the end of the culturing. A minor decrease in insulin secretion was observed in some of the infected cultures. The infection was invariably associated with an increase in the expression of HLA class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…In contrast, interferon-a (IFN-a)-a cytokine that is only induced during virus infections-has been found in b cells in diabetic patients, suggesting that a virus may be present in b cells [Huang et al, 1995]. Enteroviruses can also infect b cells in culture and can induce the expression of IFN-a and HLA molecules in b cells [Parkkonen et al, 1992;Roivainen et al, 2000;Chehadeh et al, 2000a].…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, interferon-a (IFN-a)-a cytokine that is only induced during virus infections-has been found in b cells in diabetic patients, suggesting that a virus may be present in b cells [Huang et al, 1995]. Enteroviruses can also infect b cells in culture and can induce the expression of IFN-a and HLA molecules in b cells [Parkkonen et al, 1992;Roivainen et al, 2000;Chehadeh et al, 2000a].…”
Section: Discussionmentioning
confidence: 86%
“…The excess of CD 8-positive T cells in infiltrated islets and increased expression of molecules recognized by these cells, i.e., HLA class I molecules, on islet cells further suggests that one important mechanism by which beta cells are destroyed, is direct action of cytotoxic T cells. Given their function in destroying target cells infected by viral pathogens (41) and given the detected increase in expression of HLA class I molecules on beta cells after virus infection (42), it is interesting to speculate on possible involvement ofa virus also in triggering the autoimmune process leading to beta cell destruction, although in this case of IDDM no evidence of an association between a virus and the disease process was obtained.…”
Section: Discussionmentioning
confidence: 96%
“…This might indicate ongoing virus-induced interferon secretion in the islets. We have previously shown that enterovirus infection in human pancreatic islets leads to such class I HLA hyperexpression in vitro partly mediated by secretion of type 1 interferons (23).…”
Section: Discussionmentioning
confidence: 99%